Al-Qur'an as a Source of Knowledge in Islamic Education and Its Relevance to the Curriculum Development - Nurul Atik Hamida; Ahmad Yusam Thobroni (UIN Sunan Ampel Surabaya, 2021)
Al-Qur’an is the source of everything, because it is used as a guide in the life of Muslims, including in the Islamic education system by making the Al-Qur'an a source of knowledge (inspiration). In line with this, the form of developing an Islamic education curriculum should also make the Al-Qur'an the main basis for producing superior human beings. This study aims to examine the Al-Qur'an as a source of knowledge in education, as well as explore its relevance in the development of Islamic education curriculum. This study uses a qualitative research model by conducting a literature study. The data was collected from the verses of the Al-Qur'an with the maudhu'i interpretation method. The results of this study found the relevance between the objectives of the educational curriculum and the development of the Islamic education curriculum through the verses; 1) QS. al-'Alaq: 1-5 which implies that students can acquire knowledge continuously through reading (literacy), both written and unwritten; 2) QS. al-Baqarah: 31 suggests that through teaching, students can gain a variety of knowledge so that they are worthy of being a leader; 3) QS. al-Nahl: 78 suggests, by honing abilities and skills through hearing, seeing, and the heart (the three capitals possessed by humans), students can hone their abilities and skills; 4) QS. Luqma>n: 13-19 hints at the importance of practicing morals in life for students by ordering prayer, enforcing amar ma'ruf nahi munkar, not being arrogant, and polite when communicating.